2010
DOI: 10.1007/s00284-010-9744-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Characterization of an Extracellular Leucine Aminopeptidase from Aspergillus oryzae

Abstract: Leucine aminopeptidase (LAP), an enzyme used in the food industry, is an exopeptidase that removes an amino acid residue, primarily leucine (Leu), from the N-terminus of peptides and protein substrates. In this study, we focused on the leucine aminopeptidase A (lapA) gene from Aspergillus oryzae RIB40. To purify and characterize the LapA, lapA was overexpressed in A. oryzae RIB40 using the amyB promoter. LAP activity in the culture supernatant of one transformant harboring the lapA expression plasmid was 33 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The enzyme was not inhibited by the addition of EDTA, indicating that metal ions are not necessary for the activity of the protease from A. oryzae LBA 01. Matsushita-Morita et al [6] reported that a protease from A. oryzae ATCC 42149 was activated in the presence of the metal ions Zn 2+ and Co 2+ at final concentrations of 1 mM. In the same study, the addition of 1 mM Ca 2+ , Mg 2+ , or Mn 2+ inhibited the enzyme.…”
Section: Effects Of Various Salts and Compounds On The Proteasementioning
confidence: 85%
See 1 more Smart Citation
“…The enzyme was not inhibited by the addition of EDTA, indicating that metal ions are not necessary for the activity of the protease from A. oryzae LBA 01. Matsushita-Morita et al [6] reported that a protease from A. oryzae ATCC 42149 was activated in the presence of the metal ions Zn 2+ and Co 2+ at final concentrations of 1 mM. In the same study, the addition of 1 mM Ca 2+ , Mg 2+ , or Mn 2+ inhibited the enzyme.…”
Section: Effects Of Various Salts and Compounds On The Proteasementioning
confidence: 85%
“…Aspergillus oryzae (A. oryzae) is a filamentous fungus listed as a "Generally Recognized as Safe (GRAS)" organism by the US Food and Drug Administration. It has a long history of use in the food industry in the production of traditional fermented foods, due to its high proteolytic activity and its use of sugar [5,6]. According to Machida et al [7] the molecular history of the organism shows that A. oryzae has the largest expansion of hydrolytic genes (135 proteinase genes).…”
Section: Introductionmentioning
confidence: 99%
“…An extracellular leucine aminopeptidase from A. oryzae RIB40 was described previously by Matsushita et al 40 Here, the aminopeptidase exhibited the highest activity at pH 8.5 and 60°C and showed a molecular weight of 33 kDa by SDS-PAGE analysis. 40 A leucine aminopeptidase 1 from A. oryzae ATCC 20386 was purified and characterized by Nakadai et al 41 Again, the enzyme exhibited the highest enzyme activity at pH 8.5 and 60°C. However, in contrast to our observations, the native size determined was 26.5 kDa by SEC analysis.…”
Section: Articlementioning
confidence: 97%
“…Consequently, the genome analysis of A. oryzae and its post-genome research revealed novel enzymes that may be involved in the degradation of proteins of the start material of fermented food. In the same approach, a novel leucine aminopeptidase from A. oryzae, which has broad substrate specificity mainly for the release of leucine from the amino-termini of peptides, were identified in A. oryzae 12 . Some of the novel proteases are also identified 13,14 in the same strategy.…”
Section: Post-genomic Approach Of a Oryzae And Identification Of Newmentioning
confidence: 99%